Pengaruh Jenis Material Cutter Slot Drill Terhadap Hasil Regrinding dan Tool Life - AGUNG DWI SAPTO; Kurnia Yogo Utomo (Jurnal Rekayasa Mesin, 2021)
Damage cutting tools on CNC machines is a common problem that is often encountered in the field of machining industry. Long tool life can certainly save the expenditure of the company because minimizing the purchase of new cutting tools because of the damage, for that this research aims to help estimate the age of cutting tools on slot cutter drill short type of carbide and HSS and get an idea of how long the cutter can be used and know the impact of the regrinding process on the cutting tools. In this study used quantitative methods where research focused on the use of data analysis software computer cutting and data service and also manually calculation results presented in the form of tables and graphs. The results obtained by carbide cutters have a longer tool life of 706 minutes compared with a cutter HSS 162 minutes to achieve a degree of stroke-0.1 mm and the regrinding process leads to the reduction of feeding speed, cutting speed and performance on the cutter.